Celery root extract as an inducer of mania induction in a patient on venlafaxine and St John's Wort. Issue 7 (2nd October 2016) - Khalid, Zaira; Osuagwu, Ferdnand C.; Shah, Bilal; Roy, Nikita; Dillon, James E.; Bradley, Ronald
ABSTRACT: Celery root belongs to a group of plants classified as the umbelliferous family, which contains phytoestrogens. Phytoestrogens are structurally similar to estrogen as they share a pair of hydroxyl groups and phenolic ring, which enables them to bind to estrogen receptors directly, making them a herbal remedy for low estrogen states such as menopause. We present a case of a female patient with depression who was stabilized on venlafaxine and St John's Wort, and who developed a manic episode due to elevated serum venlafaxine levels after she started taking celery extracts for menopausal related issues. We proffer a hypothesis for this unusual occurrence.